MARKETING TOOLS FOR ENSURING ECONOMIC SECURITY OF ADVERTISING BUSINESS IN THE DIGITAL ENVIRONMENT - ZAITSEVA, Olena; HAVLOVSKA, Nataliia; CHUMAK, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to a thorough analysis of marketing tools that are used to ensure the economic security of advertising business enterprises in the digital environment. Features of consumption in the digital age and new opportunities for advertising business are determined. An analysis of general and specific security risks in the advertising business was carried out. Relevant marketing tools for ensuring the economic security of enterprises in the creative sphere are proposed. The main types of general and specific security risks in the advertising business are highlighted. Global fluctuations and the cyclic nature of the development of the national economy. Development of technologies and diffusion of innovations. Changing values, tastes and consumer requests. Aggressive actions of competitors and activity of other market agents. Unforeseen political conditions and changes in legislation. Risk of non-fulfillment of obligations to clients/customers (non-compliance with deadlines, other conditions, appropriate fines and increased costs). Unforeseen insolvency of clients/customers. Unreasonableness and mistakes in planning an advertising campaign. Insufficient awareness of the cross-cultural differences of the countries, regions, and local territories where the advertising campaign will take place. Reputational risks, cancellation (cancellation culture). Force majeure circumstances. Emphasis is placed on the fact that the use of the proposed marketing tools will allow the advertising business not only to function successfully in changing modern conditions, but also to proactively take corrective measures in order to prevent a dangerous situation or take targeted actions to reduce the consequences of possible risks.